Morphometric and molecular genetic studies on rhinoceros beetle (Oryctes rhinoceros linnaeus) populations in oil palm plantations - Gnanasegaram, Manjeri (2013)
Oryctes rhinoceros, commonly known as the rhinoceros beetle is an important agricultural pest that is known to inflict serious damage on young oil palm trees. Control and trapping procedures in plantations nationwide commonly incorporate the usage of pheromone lures. However, beetles were widely assumed to exhibit selective attraction level towards the pheromone lures. This initiated the interest to study the population structure of O. rhinoceros via morphometric and population genetic studies to assess the possible occurrence of a cryptic complex. Samples of O. rhinoceros beetles were collected from young oil palm replanting sites at Felcra Berhad, Perak, Tennamaram Estate; Selangor, Kuantan Trading Plantation; Pahang and Paya Pinang Plantation; Medan using a light trap and also a pheromone trap at each site. A working hypothesis is that beetles trapped by each procedure correspond, respectively, to different populations. Morphometric studies were carried out based on the measurements of total body length, elytron length, width of pronotum, length of pronotum and length of cephalic horn. Based on this study, individuals from the six populations were observed to overlap with one another in the scatter plot produced by the principal component analysis and the canonical discriminant analysis, highlighting that the populations are morphologically indistinguishable. Meanwhile, population genetic studies were carried out using random amplified microsatellite (RAM) markers and also single locus deoxyribonucleic acid (DNA) microsatellite markers. In the RAMs study, a total of 78 reproducible, polymorphic loci were generated using seven RAMs primers. Similarity in geographical location, as well as the possible occurrence of two groups in O. Rhinoceros (the putative pheromone and light group) could have influenced the clustering pattern of the populations. However, the clustering did not diagnostically group any O. rhinoceros population to provide a clear evidence of a cryptic species complex. Next, using the 5’ anchored random amplified microsatellites-polymerase chain reaction (RAMs-PCR) technique, a total of 180 microsatellite repeat motifs were isolated and a total of 144 primer pairs were designed. The isolated repeat motifs consisted of 151 perfect repeats, 14 interrupted repeats, 10 compound repeats,three interrupted compound repeats, one interrupted complex repeat and one complex repeat. After thorough optimizations of the developed markers, a total of 30 polymorphic single locus DNA microsatellite markers were identified and used to screen through the six populations of O. rhinoceros. Using these microsatellite markers, a total of 84 alleles were successfully amplified with molecular weights ranging from 113 bp to 328 bp. The number of alleles per locus ranged from two to eight alleles. The observed heterozygosities ranged from 0.0335 to 0.9333. The polymorphic information content (PIC) for the 30 loci ranged from 0.0478 to 0.7461. Further analysis on the variations within and between populations indicated a randomly mating population with free exchange of genes. Variations within populations were higher than between populations. The clustering pattern of the populations was observed to be influenced by similarity in geographical location and possible events of migration. In this study, the population structure of the O. rhinoceros beetles has been exhaustively studied based on morphometric analysis and also molecular markers. It has been ascertained that there is no possible cryptic complex occurring in the O. rhinoceros populations studied.